Assessment of social support systems of patients, those have the alcohol use problem - Yüncü, Zeki; Yıldız, Umut; Kesebir, Sermin; Altıntoprak, Ender; Coşkunol, Hakan (Journal of Dependence, 2005)
Objective: Family, friends and social environment play an important role during the alcohol abuse period and treatment. Despite this, the focus of alcohol treatment units is inpatients. This causes the families and social network to be overlooked and / or not to take the necessary role in the treatment. By this way this group, who has an important role in the provision and sustain of sobriety, is ignored. In this study, our objective is to research the social support systems of the alcohol use disorder (AUD) cases according to some socio-demographical aspects. Method: The inpatients in the Ege University Dependency Unit are taken as the cases. SCID-1 has been applied to these cases according to DSM IV. The cases having the AUD have filled the socio-demographic information form, social network list, perceived friend inventory (PSS_Fr) and perceived family inventory. (PSS_Fa) These cases have been classified according to the age of onset alcohol use, to the existence of any psychiatric disorder’s in their family, to the marital status, and to the existence of comorbid psychiatric disorders. Results: 40 alcohol disorder inpatients were included in this study. The number of confidants in the social network and the PPS_Fa scores is higher in married subjects than singles. This difference is statistically significant. (0.034; 0.035 in order). The group, which has the AUD comorbid anxiety disorder, reported higher number of relatives compared to the groups, which have only AUD, AUD comorbid major depressive disorder and multiple substance use disorder. This difference is statistically significant. (0.018). The family support according to the marital status in terms of relative and confidant number and the difference between the single and married is statistically meaningful. In terms of DSM IV diagnosis, onset of alcohol, the parent’s educational levels, the existence of any psychiatric disorder’s there has not been detected any statistically meaningful difference. Conclusion: The married individuals, who have the AUD, report more confidants and family support than singles. However, more studies with more subjects are needed.